Corporate innovation and innovation efficiency: does religion matter?. Issue 2 (6th June 2016) - Huang, Dan; Lu, Dong; Luo, Jin-hui
Abstract : Purpose: The purpose of this paper is to examine whether and how the extent of religion in a firm's social environment affects corporate innovation and innovation efficiency from the perspectives of religion-related risk aversion and religion-based social norms. Design/methodology/approach: Using a sample of 8, 601 Chinese firm-year observations from 2007 to 2012, this paper examines the relationship between religion and innovation intensity, as well as innovation efficiency. A battery of checks, that is, adopting Heckman selection model, using a province-level measure of religiosity and an alternative measure of innovation intensity, and taking the stochastic frontier analysis method to capture corporate innovation efficiency, are conducted to alleviate the concern of self-selection and to guarantee the robustness of the findings of this paper. Findings: This paper finds strong evidence that firms registered in more religious regions, that is, regions with more Buddhist monasteries within a certain radius, undertake fewer innovation activities as measured by the ratio of R&D investment over total sales income but achieve higher innovation efficiency reflected by the value-relevance of R&D investment. Originality/value: This paper complements the existing literature by suggesting that religion can serve as an informal social mechanism and performs a "less is more" effect in disciplining corporate innovation activities.